Underground metabolism facilitates the evolution of novel pathways for vitamin B6 biosynthesis - Richts, Björn (Appl Microbiol Biotechnol, 2021)
ABSTRACT: The term vitamin B6 is a designation for the vitamers pyridoxal, pyridoxamine, pyridoxine and the respective phosphate esters pyridoxal-5′-phosphate (PLP), pyridoxamine-5′-phosphate and pyridoxine-5′-phosphate. Animals and humans are unable to synthesise vitamin B6. These organisms have to take up vitamin B6 with their diet. Therefore, vitamin B6 is of commercial interest as a food additive and for applications in the pharmaceutical industry. As yet, two naturally occurring routes for de novo synthesis of PLP are known. Both routes have been genetically engineered to obtain bacteria overproducing vitamin B6. Still, major genetic engineering efforts using the existing pathways are required for developing fermentation processes that could outcompete the chemical synthesis of vitamin B6. Recent suppressor screens using mutants of the Gram-negative and Gram-positive model bacteria Escherichia coli and Bacillus subtilis, respectively, carrying mutations in the native pathways or heterologous genes uncovered novel routes for PLP biosynthesis. These pathways consist of promiscuous enzymes and enzymes that are already involved in vitamin B6 biosynthesis. Thus, E. coli and B. subtilis contain multiple promiscuous enzymes causing a so-called underground metabolism allowing the bacteria to bypass disrupted vitamin B6 biosynthetic pathways. The suppressor screens also show the genomic plasticity of the bacteria to suppress a genetic lesion. We discuss the potential of the serendipitous pathways to serve as a starting point for the development of bacteria overproducing vitamin B6. KEY POINTS: • Known vitamin B6 routes have been genetically engineered. • Underground metabolism facilitates the emergence of novel vitamin B6 biosynthetic pathways. • These pathways may be suitable to engineer bacteria overproducing vitamin B6.